A generalized hydrodynamical Gurevich-Zybin equation of Riemann type and its Lax type integrability - Pavlov, M.V.; Prykarpatsky, A.K. (Condensed Matter Physics, 2010)
This paper is devoted to the study of a hydrodynamical equation of Riemann type, generalizing the remarkable Gurevich–Zybin system. This multi-component non-homogenous hydrodynamic equation is characterized by the only characteristic flow velocity. The compatible bi-Hamiltonian structures and Lax type representations of the 3-and 4-component generalized Riemann type hydrodynamical system are analyzed. For the first time the obtained results augment the theory of integrability of hydrodynamic type systems, originally developed only for distinct characteristic velocities in homogenous case. Досліджено гідродинамічне рівняння типу Рімана, що узагальнює відому систему Гуревича - Зибіна. Це багатокомпонентне гідродинамічне рівняння характеризується єдиною характеристичною швидкістю потоку. Проаналізовані сумісні бі-гамільтонові структури та представлення Лакса для три- та чотирикомпонентної узагальненої гідродинамічної системи типу Рімана. Одержані результати вперше доповнюють теорію інтегровності систем гідродинамічного типу, раніше розвиненої тільки для відмінних швидкостей в однорідному випадку.